Remote loading paclitaxel-doxorubicin prodrug into liposomes for cancer combination therapy - Jiang Yu; Yingli Wang; Shuang Zhou; Jinbo Li; Jiamei Wang; Dongxu Chi; Xue Wang; Guimei Lin; Zhonggui He; Yongjun Wang (Elsevier, 2020)
The combination of paclitaxel (PTX) and doxorubicin (DOX) has been widely used in the clinic. However, it remains unsatisfied due to the generation of severe toxicity. Previously, we have successfully synthesized a prodrug PTX-S-DOX (PSD). The prodrug displayed comparable in vitro cytotoxicity compared with the mixture of free PTX and DOX. Thus, we speculated that it could be promising to improve the anti-cancer effect and reduce adverse effects by improving the pharmacokinetics behavior of PSD and enhancing tumor accumulation. Due to the fact that copper ions (Cu2+) could coordinate with the anthracene nucleus of DOX, we speculate that the prodrug PSD could be actively loaded into liposomes by Cu2+ gradient. Hence, we designed a remote loading liposomal formulation of PSD (PSD LPs) for combination chemotherapy. The prepared PSD LPs displayed extended blood circulation, improved tumor accumulation, and more significant anti-tumor efficacy compared with PSD NPs. Furthermore, PSD LPs exhibited reduced cardiotoxicity and kidney damage compared with the physical mixture of Taxol and Doxil, indicating better safety. Therefore, this novel nano-platform provides a strategy to deliver doxorubicin with other poorly soluble antineoplastic drugs for combination therapy with high efficacy and low toxicity.